Navigating the Uncommon: Case Report of Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC) Successfully Managed with Implantable Cardioverter Defibrillator (ICD) - Purwowiyoto, Sidhi Laksono; Hermawan; Kusharsamita, Hillary (UNUSA Press, 2024)
With a high risk of sudden cardiac mortality, arrhythmogenic right ventricular cardiomyopathy (ARVC) is a rare inherited cardiomyopathy characterized by right ventricular dysfunction and ventricular arrhythmias (VA). In this case study, a 35-year-old presented with palpitations and revealed epsilon waves on the right precordial electrocardiogram (ECG) leads which led to the suspicion of ARVC. A 24-hour Holter monitoring revealed frequent ventricular extrasystoles (>500 per 24 hours), a CMRI revealed RV dyskinesia and transmural LGE in the apical RV, and an electrophysiologic study detected spontaneous polymorphic ventricular tachycardia (VT) despite the presence of induction ventricle fibrillation (VF). These results validated the diagnosis of ARVC and indicated that an implantable cardioverter defibrillator was necessary treatment. The ability to identify potential ARVC’s ECG abnormalities, the timing to pursue further studies, and determining necessary treatment execution are critical. The evaluation of cardiac, electrophysiological, and clinical imaging parameters is essential for the risk stratification, diagnosis, and management of patients with ARVC.